2017
DOI: 10.3390/ijerph14060656
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Long-Term Strategy for Voluntary-Based Internal Radiation Contamination Monitoring: Representativeness of the Monitoring Results in Fukushima, Japan

Abstract: Following Japan’s 2011 Fukushima nuclear incident, voluntary participation, rather than mandatory, was adopted as the default scenario for individual radiation monitoring. We evaluated the representativeness of the internal monitoring results from voluntary participants in Minamisoma City, which is located 10–40 km from the Fukushima nuclear plant. Of approximately 70,000 individuals who were residing in Minamisoma City before the incident, a total of 19,263 residents (aged ≥21 years) participated in the monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This finding is comparable with the previously reported results for adults and children in Minamisoma City. 29) Although additional doses from foods were reported to be negligible (50.002 mSv/y in 2014) in market basket and duplicate portion studies, 30) the present results also showed that chronic internal exposure is wellmanaged through food contamination control and that internal exposure has a negligible health risk for children aged 0-6 years. Although infants/small children might have different dietary patterns from adults, internal contamination is still well-controlled.…”
Section: Discussionsupporting
confidence: 46%
“…This finding is comparable with the previously reported results for adults and children in Minamisoma City. 29) Although additional doses from foods were reported to be negligible (50.002 mSv/y in 2014) in market basket and duplicate portion studies, 30) the present results also showed that chronic internal exposure is wellmanaged through food contamination control and that internal exposure has a negligible health risk for children aged 0-6 years. Although infants/small children might have different dietary patterns from adults, internal contamination is still well-controlled.…”
Section: Discussionsupporting
confidence: 46%
“…The radiological countermeasures assessed in this study included WBC, food inspection, air dose monitoring, individual dose monitoring, basic survey, thyroid examination (specific to the examination under the FHMS), and explanatory meetings. WBC is the monitoring of internal radiation exposure and provides opportunities for the experts and examinees to exchange the individual dose information [ 20 , 25 ]. Food inspection is the measurements of radionuclide concentrations in foods.…”
Section: Methodsmentioning
confidence: 99%
“…These activities identified radiation risks and they also addressed radiation anxiety, comprehensive health risks to individuals, and well-being [ 20 ] and were well in accordance with the concept of risk communication, which has been defined by the National Research Council as “an interactive process of exchange of information and opinion among individuals” [ 24 ]. For example, whole body counter (WBC), i.e., the monitoring of internal radiation exposure, was first used to measure levels of internal radiation doses for medical interventions but then became a tool for risk communication: the WBC creates the opportunity for experts to discuss radiation directly with individuals and address their concerns [ 20 , 25 ]. In addition to radiation monitoring of foods and air dosages, “individual” dose monitoring has been performed by collecting and providing external radiation exposure data using devices such as glass badges [ 4 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were compared with 134 Cs and 137 Cs levels measured from October 2011 to March 2015 for voluntary participants. They found sufficient agreement between simulated and measured 134 Cs and 137 Cs levels except for 134 Cs in October 2011 and concluded that the voluntary monitoring participant group was a good representative sample [72].…”
Section: Issues Related To Internal Dose Assessmentmentioning
confidence: 98%
“…As mentioned in previous subsection, "interpretation of personal dose measurement results", representativeness of subjects is one of the concerns about volunteer-based monitoring. Representativeness of WBC subjects was investigated by Nomura et al [72]. Based on regression projection techniques, separate probabilities for 137 Cs and 134 Cs detection for a whole population were simulated.…”
Section: Issues Related To Internal Dose Assessmentmentioning
confidence: 99%